A partitioned solver to simulate large-displacement fluid–structure interaction of thin plate systems for vibration energy harvesting. (November 2019) - Chawdhury, Samir; Morgenthal, Guido
Highlights: A 2D partitioned solver for fluid–structure interaction of cantilevered thin plates. The coupling of 2D vortex particle methods with 2D corotational beam element. Study on the potential of thin plate systems for aeroelastic energy harvesting. Large-amplitude flapping of inverted and T-shaped cantilevers with/without tip mass. Identification of efficient cantilever harvesters depending on the target wind speeds. Abstract: A two-dimensional (2D) partitioned solver is extended for large-displacement fluid–structure interaction (FSI) simulations of thin plate systems, particularly to investigate their potential of aeroelastic energy harvesting. The 2D vortex particle method with immersed interface technique and adaptive solution strategy is used for analyzing flow around deformable bodies; three-dimensional edge effects are ignored. The geometrically nonlinear plate motion is analyzed using 2D corotational beam element. The coupled solver is validated on benchmark large-displacement FSI problems such as flag-type flapping of cantilever plates in axial flow and Kármán vortex street. The validated solver is used further to perform a comparative study on different cantilever systems to obtain guidelines for the design of experimental set-ups of prototype harvesters. The changes in aerodynamic behavior and flapping pattern of inverted and T-shaped cantilevers with/without tip mass are investigated. The simulations are performed for increasing wind speeds until the permanent deflection mode occurs. The influences of damping ratios are analyzed as preliminary studies to investigate the electrical damping effects of harvesters. The influential parameters such as response amplitude and oscillating frequency are compared to identify not only efficient cantilever harvesters but also an appropriate combination of physical and electrical parameters depending on target wind speeds.